(untitled) (Nexo Revista Científica, 2021)
Broadband highways are being built in major cities around the world to combat traffic congestion. At the same time, existing buildings are demolished or powerful overpasses are raised above them. However, it often turns out that newly created highways quickly exhaust their capacity, and traffic jams are formed on them again. This situation indicates that increasing the capacity of the highway does not solve the problem of traffic jams, but often aggravates it, since as a result of this increase, even more cars are drawn to the highway from adjacent territories, often exceeding their current capacity. At the same time, the streets in the surrounding areas are empty and their potential is not used to the full extent. This situation has arisen due to the disruption of the city road network by lengthy obstacles in the form of ravines, rivers, floodplains of small rivers, and railways. This situation can be corrected by "stitching" the streets over the gaps by building bridges and overpasses with a capacity corresponding to the capacity of the "stitched" streets. Most of the gaps fall on relatively small streets, which approach the banks of fairly wide floodplains of small rivers and streams, and this makes it advisable to build mainly small (with a span of 20-25 m) and relatively inexpensive bridges, with the number of spans sufficient to cover the floodplain and reach the levels of road surfaces of connected streets. There will be several hundred such bridges over the river barriers in a large city, for example, Moscow, and several hundred more, taking into account the required number of them over the railways, and in the end, about a thousand. It is proposed to erect bridge buildings instead of simple road bridges. Such structures combine two city functions; the first of them is transport, the second is public, residential, or economic, depending on the needs of the city and the environmental situation at the construction site. An important requirement for the second function is a quick return on the financial assets invested in the construction and income from the operation of the building acceptable to the investor. The bridge part of a bridge building should become the property of the city.